Method for detecting hollow fibers in electronic-grade glass fiber cloth
By using a mixed solution prepared by benzyl alcohol and anhydrous ethanol, the hollow fibers in the electronic grade glass fiber cloth were detected, and the problem of inaccurate detection results in the prior art was solved, and higher detection accuracy and efficiency were achieved.
Patent Information
- Application Number
- CN202510019328.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, when using benzyl alcohol solution to detect hollow fibers in electronic grade glass fiber cloth, the detection results are inaccurate and cannot meet the needs of high-performance electronic materials.
A mixed solution is prepared by benzyl alcohol and anhydrous ethanol, so that its light refractive index is close to that of the glass fiber cloth, so that the hollow fiber can be accurately detected.
By adjusting the mass ratio of benzyl alcohol, anhydrous ethanol and surfactant in the mixed solution, it can adapt to different types of glass fiber cloths, improving the accuracy and efficiency of hollow fiber detection.
Smart Images

Figure BDA0005230840300000061 
Figure BDA0005230840300000071 
Figure BDA0005230840300000072
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass fibers, and in particular to a method for detecting hollow fibers in electronic-grade glass fiber cloth. Background Art
[0002] At present, benzyl alcohol solution is usually used as a solution for detecting the hollow fibers of E-glass fiber cloth, because the optical refractive index of E-glass fiber cloth is similar to that of benzyl alcohol solution. However, as electronic information products develop towards high performance, lightness, and miniaturization, the performance requirements for electronic-grade glass fiber cloth are becoming higher and higher. Electronic-grade glass fiber cloth is developing towards higher strength, lower dielectric constant, lower dielectric loss, better heat resistance and chemical resistance to meet the demand for high-performance electronic materials in high-end fields such as 5G communications, artificial intelligence, and new energy vehicles. Therefore, Low DK series glass fiber cloth products and quartz series glass fiber cloth products were born. However, due to the difference in the optical refractive index of different glass fiber cloths, the expected effect cannot be achieved by only using benzyl alcohol solution to detect the hollow fibers in the product. The test results are often inconsistent with the actual number of hollow fibers in the electronic-grade glass fiber cloth, and the test results are inaccurate.
[0003] In view of the above-mentioned difficulties, it is urgent to propose a method for detecting hollow fibers of electronic-grade glass fiber cloth to solve the problems existing in the prior art. Summary of the invention
[0004] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art and provide a method for detecting hollow fibers in electronic-grade glass fiber cloth, using benzyl alcohol solution and anhydrous ethanol to prepare a mixed solution so that its optical refractive index is close to that of the glass fiber cloth, thereby being able to detect the hollow fibers in the glass fiber cloth and ensuring the accuracy of the detection results.
[0005] The technical solution of the present invention is:
[0006] The method for detecting hollow fibers in electronic grade glass fiber cloth comprises the following steps:
[0007] S1 sampling;
[0008] S2 prepares a mixed solution of benzyl alcohol and anhydrous ethanol;
[0009] S3: soaking the sample in step S1 in the mixed solution in step S2;
[0010] S4 observes the number of bright lines in the sample under light, which is the number of hollow fibers in the electronic grade glass fiber cloth.
[0011] Preferably, in step S2, for Low Dk series glass fiber cloth, the mass ratio of benzyl alcohol to anhydrous ethanol is 100:(19-23); for quartz series glass fiber cloth, the mass ratio of benzyl alcohol to anhydrous ethanol is 100:(28-32).
[0012] Preferably, in step S2, the mixed solution further includes a surfactant, and for glass fiber cloths of the Low Dk series and the quartz series, the mass ratio of benzyl alcohol to the surfactant is 100:(0.5-1.5).
[0013] Preferably, the surfactant is polyoxyethylene octylphenol ether.
[0014] Preferably, in step S3, the soaking time is 40-60 minutes.
[0015] Preferably, in step S1, when sampling, 5 samples with a size of 15 cm×25 cm in the warp direction×weft direction are taken from the entire cloth width.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] 1. The light refractive index (1.45-1.5) of Low DK series glass fiber cloth products and quartz series glass fiber cloth products is lower than the light refractive index (1.538-1.541) of benzyl alcohol solution. When light is irradiated on the glass fiber cloth surface soaked with benzyl alcohol solution, the bright line of hollow fiber will not appear, because now the glass fiber cloth is not soaked in by benzyl alcohol solution (glass fiber cloth is completely soaked in when presenting transparent state in solution). And the light refractive index (1.3611) of absolute ethanol is lower than LowDK series products and quartz series products. When benzyl alcohol solution and absolute ethanol are mixed in a certain ratio, the light refractive index of mixed solution is close to glass fiber cloth. Now glass fiber cloth will be completely soaked. When light is irradiated on the glass fiber cloth surface, hollow fiber state will be presented. Therefore, the present invention uses benzyl alcohol solution and absolute ethanol to be mixed with mixed solution, so that its light refractive index is close to glass fiber cloth, so that the hollow fiber in glass fiber cloth can be detected, and the accuracy of the test result is guaranteed.
[0018] 2. In the present invention, by changing the mass ratio of each organic solvent in the mixed solution, the light refractive index will change to different degrees, which is suitable for the detection of different types of glass fiber cloth hollow fibers. In addition, by adding a surfactant to the mixed solution, the present invention can improve the detection efficiency of the hollow fiber and shorten the detection time by more than 30%. DETAILED DESCRIPTION
[0019] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0020] Example 1
[0021] The method for detecting hollow fibers in electronic-grade glass fiber cloth of this embodiment comprises the following steps:
[0022] S1 Sampling: Take 10 samples of 15cm×25cm in warp and weft directions from the entire width of Low Dk series glass fiber cloth (LD1078, LD1035, LD1037, LD1080, LD2116, LD3313);
[0023] S2 prepared 600 mL of a mixed solution of benzyl alcohol and anhydrous ethanol in a mass ratio of 100:19 (wherein the volumes of benzyl alcohol and anhydrous ethanol were 480 mL and 120 mL, respectively), and 600 mL of a mixed solution of benzyl alcohol, anhydrous ethanol and polyoxyethylene octylphenol ether in a mass ratio of 100:19:0.5 (wherein the volumes of benzyl alcohol, anhydrous ethanol and polyoxyethylene octylphenol ether were approximately 478 mL, 120 mL and 2 mL, respectively); placed the prepared mixed solutions in a sample tray with black rubber for standby use;
[0024] S3: dividing the sample in step S1 into two equal parts, and soaking each of them in the two mixed solutions in step S2 for 60 minutes;
[0025] S4 Use tweezers to clamp the edge of the glass fiber cloth, place the sample under a strong light, adjust the sample position so that the light is in a side light state on the glass fiber cloth, and the hollow fibers in it will appear bright; observe and record the number of bright lines that appear when the sample is immersed for 10min, 20min, 40min, and 60min under light, which is the number of hollow fibers in the electronic-grade glass fiber cloth.
[0026] Example 2
[0027] The method for detecting hollow fibers in electronic-grade glass fiber cloth of this embodiment comprises the following steps:
[0028] S1 Sampling: Take 10 samples of 15cm×25cm in warp and weft directions from the entire width of Low Dk series glass fiber cloth (LD1078, LD1035, LD1037, LD1080, LD2116, LD3313);
[0029] S2 prepared 600 mL of a mixed solution of benzyl alcohol and anhydrous ethanol in a mass ratio of 100:21 (wherein the volumes of benzyl alcohol and anhydrous ethanol were approximately 476 mL and 124 mL, respectively), and 600 mL of a mixed solution of benzyl alcohol, anhydrous ethanol and polyoxyethylene octylphenol ether in a mass ratio of 100:21:1 (wherein the volumes of benzyl alcohol, anhydrous ethanol and polyoxyethylene octylphenol ether were approximately 472 mL, 123 mL, and 5 mL, respectively); placed the prepared mixed solutions in a sample tray with black rubber for standby use;
[0030] S3: dividing the sample in step S1 into two equal parts, and soaking each of them in the two mixed solutions in step S2 for 60 minutes;
[0031] S4 Use tweezers to clamp the edge of the glass fiber cloth, place the sample under a strong light, adjust the sample position so that the light is in a side light state on the glass fiber cloth, and the hollow fibers in it will appear bright; observe and record the number of bright lines that appear when the sample is immersed for 10min, 20min, 40min, and 60min under light, which is the number of hollow fibers in the electronic-grade glass fiber cloth.
[0032] Example 3
[0033] The method for detecting hollow fibers in electronic-grade glass fiber cloth of this embodiment comprises the following steps:
[0034] S1 Sampling: Take 10 samples of 15cm×25cm in warp and weft directions from the entire width of Low Dk series glass fiber cloth (LD1078, LD1035, LD1037, LD1080, LD2116, LD3313);
[0035] S2 prepared 600 mL of a mixed solution of benzyl alcohol and anhydrous ethanol in a mass ratio of 100:23 (wherein the volumes of benzyl alcohol and anhydrous ethanol were approximately 461 mL and 139 mL, respectively), and 600 mL of a mixed solution of benzyl alcohol, anhydrous ethanol and polyoxyethylene octylphenol ether in a mass ratio of 100:23:1.5 (wherein the volumes of benzyl alcohol, anhydrous ethanol and polyoxyethylene octylphenol ether were approximately 456 mL, 137 mL, and 7 mL, respectively); placed the prepared mixed solutions in a sample tray with black rubber for standby use;
[0036] S3: dividing the sample in step S1 into two equal parts, and soaking each of them in the two mixed solutions in step S2 for 60 minutes;
[0037] S4 Use tweezers to clamp the edge of the glass fiber cloth, place the sample under a strong light, adjust the sample position so that the light is in a side light state on the glass fiber cloth, and the hollow fibers in it will appear bright; observe and record the number of bright lines that appear when the sample is immersed for 10min, 20min, 40min, and 60min under light, which is the number of hollow fibers in the electronic-grade glass fiber cloth.
[0038] Example 4
[0039] The method for detecting hollow fibers in electronic-grade glass fiber cloth of this embodiment comprises the following steps:
[0040] S1 Sampling: Take 10 samples of 15cm×25cm in warp and weft directions from the entire width of the quartz series glass fiber cloth (TQ1078, TQ1035, TQ2118);
[0041] S2 prepared 600 mL of a mixed solution of benzyl alcohol and anhydrous ethanol in a mass ratio of 100:28 (wherein the volumes of benzyl alcohol and anhydrous ethanol were approximately 440 mL and 160 mL, respectively), and 600 mL of a mixed solution of benzyl alcohol, anhydrous ethanol and polyoxyethylene octylphenol ether in a mass ratio of 100:28:0.5 (wherein the volumes of benzyl alcohol, anhydrous ethanol and polyoxyethylene octylphenol ether were approximately 438 mL, 160 mL, and 2 mL, respectively); placed the prepared mixed solutions in a sample tray with black rubber for standby use;
[0042] S3: dividing the sample in step S1 into two equal parts, and soaking each of them in the two mixed solutions in step S2 for 60 minutes;
[0043] S4 Use tweezers to clamp the edge of the glass fiber cloth, place the sample under a strong light, adjust the sample position so that the light is in a side light state on the glass fiber cloth, and the hollow fibers in it will appear bright; observe and record the number of bright lines that appear when the sample is immersed for 10min, 20min, 40min, and 60min under light, which is the number of hollow fibers in the electronic-grade glass fiber cloth.
[0044] Example 5
[0045] The method for detecting hollow fibers in electronic-grade glass fiber cloth of this embodiment comprises the following steps:
[0046] S1 Sampling: Take 10 samples of 15cm×25cm in warp and weft directions from the entire width of the quartz series glass fiber cloth (TQ1078, TQ1035, TQ2118);
[0047] S2 prepared 600 mL of a mixed solution of benzyl alcohol and anhydrous ethanol in a mass ratio of 100:30 (wherein the volumes of benzyl alcohol and anhydrous ethanol were approximately 430 mL and 170 mL, respectively), and 600 mL of a mixed solution of benzyl alcohol, anhydrous ethanol and polyoxyethylene octylphenol ether in a mass ratio of 100:30:1 (wherein the volumes of benzyl alcohol, anhydrous ethanol and polyoxyethylene octylphenol ether were approximately 427 mL, 169 mL, and 4 mL, respectively); placed the prepared mixed solutions in a sample tray with black rubber for standby use;
[0048] S3: dividing the sample in step S1 into two equal parts, and soaking each of them in the two mixed solutions in step S2 for 60 minutes;
[0049] S4 Use tweezers to clamp the edge of the glass fiber cloth, place the sample under a strong light, adjust the sample position so that the light is in a side light state on the glass fiber cloth, and the hollow fibers in it will appear bright; observe and record the number of bright lines that appear when the sample is immersed for 10min, 20min, 40min, and 60min under light, which is the number of hollow fibers in the electronic-grade glass fiber cloth.
[0050] Example 6
[0051] The method for detecting hollow fibers in electronic-grade glass fiber cloth of this embodiment comprises the following steps:
[0052] S1 Sampling: Take 10 samples of 15cm×25cm in warp and weft directions from the entire width of the quartz series glass fiber cloth (TQ1078, TQ1035, TQ2118);
[0053] S2 prepared 600 mL of a mixed solution of benzyl alcohol and anhydrous ethanol in a mass ratio of 100:32 (wherein the volumes of benzyl alcohol and anhydrous ethanol were approximately 420.5 mL and 179.5 mL, respectively), and 600 mL of a mixed solution of benzyl alcohol, anhydrous ethanol and polyoxyethylene octylphenol ether in a mass ratio of 100:32:1.5 (wherein the volumes of benzyl alcohol, anhydrous ethanol and polyoxyethylene octylphenol ether were approximately 416 mL, 178 mL, and 6 mL, respectively); placed the prepared mixed solutions in a sample tray with black rubber for standby use;
[0054] S3: dividing the sample in step S1 into two equal parts, and soaking each of them in the two mixed solutions in step S2 for 60 minutes;
[0055] S4 Use tweezers to clamp the edge of the glass fiber cloth, place the sample under a strong light, adjust the sample position so that the light is in a side light state on the glass fiber cloth, and the hollow fibers in it will appear bright; observe and record the number of bright lines that appear when the sample is immersed for 10min, 20min, 40min, and 60min under light, which is the number of hollow fibers in the electronic-grade glass fiber cloth.
[0056] Comparative Example 1
[0057] The method for detecting hollow fibers in electronic-grade glass fiber cloth of Comparative Example 1 comprises the following steps:
[0058] S1 Sampling: Take 5 samples with the size of 15cm×25cm in the warp and weft directions from the entire width of the Low Dk series glass fiber cloth (LD1078, LD1035, LD1037, LD1080, LD2116, LD3313);
[0059] S2: soaking the sample in benzyl alcohol for 60 min;
[0060] S3 uses tweezers to hold the edge of the glass fiber cloth, places the sample under a strong light, and adjusts the position of the sample so that the light is in a side light state on the glass fiber cloth, and the hollow fibers in it will appear bright; observe and record the number of bright lines that appear when the sample is immersed for 10min, 20min, 40min, and 60min under light, which is the number of hollow fibers in the electronic-grade glass fiber cloth.
[0061] Comparative Example 2
[0062] The method for detecting hollow fibers in electronic-grade glass fiber cloth of Comparative Example 2 comprises the following steps:
[0063] S1 Sampling: Take 5 samples with a size of 15 cm × 25 cm in the warp and weft directions from the entire width of the quartz series glass fiber cloth (TQ1078, TQ1035, TQ2118);
[0064] S2: soaking the sample in benzyl alcohol for 60 min;
[0065] S3 uses tweezers to hold the edge of the glass fiber cloth, places the sample under a strong light, and adjusts the position of the sample so that the light is in a side light state on the glass fiber cloth, and the hollow fibers in it will appear bright; observe and record the number of bright lines that appear when the sample is immersed for 10min, 20min, 40min, and 60min under light, which is the number of hollow fibers in the electronic-grade glass fiber cloth.
[0066] Comparative Example 3
[0067] The difference from Example 1 is that in step S2, 600 mL of a mixed solution of benzyl alcohol and anhydrous ethanol with a mass ratio of 100:17 is prepared (wherein the volumes of benzyl alcohol and anhydrous ethanol are 488 mL and 112 mL, respectively); the prepared mixed solution is placed in a sample tray with black rubber for standby use.
[0068] Comparative Example 4
[0069] The difference from Example 1 is that in step S2, 600 mL of a mixed solution of benzyl alcohol and anhydrous ethanol in a mass ratio of 100:25 is prepared (wherein the volumes of benzyl alcohol and anhydrous ethanol are 450 mL and 150 mL, respectively); the prepared mixed solution is placed in a sample tray with black rubber for standby use.
[0070] The number of hollow fibers in the glass fiber cloth of Examples 1-6 and Comparative Examples 1-4 is shown in Table 1-2:
[0071] Table 1 Number of hollow fibers in glass fiber cloth of Examples 1-3 and Comparative Examples 1, 3-4
[0072]
[0073]
[0074] Table 2 Number of hollow fibers in glass fiber cloth of Examples 4-6 and Comparative Example 2
[0075]
[0076] It can be seen from Table 1-2 that the addition of anhydrous ethanol can reduce the optical refractive index of the mixed solution. At this time, its optical refractive index is close to that of the glass fiber cloth, which can make the hollow fiber more accurately identified. When the mass ratio of benzyl alcohol, anhydrous ethanol and surfactant is adjusted, the optical refractive index of the mixed solution can be changed, so that its optical refractive index fluctuates within a certain range, which can be applied to the detection of different types of glass fiber cloth and has a wider range of applications. In addition, it can be seen from Table 1 that only when the mass ratio of benzyl alcohol and anhydrous ethanol is within a certain range, the number of hollow fibers in the glass fiber cloth detected is relatively accurate, so the mass ratio of each component in the mixed solution is also crucial to the accuracy of the test results.
[0077] The time taken for the glass fiber cloths of Examples 1-6 to be completely soaked in different mixed solutions is shown in Table 3:
[0078] Table 3 The time for the glass fiber cloth of Examples 1-6 to be completely soaked in different mixed solutions
[0079]
[0080] In Table 3, the two mixed solutions corresponding to the Low Dk series glass fiber cloth are a benzyl alcohol / anhydrous ethanol mixed solution with a mass ratio of 100:19, and a benzyl alcohol / anhydrous ethanol / surfactant mixed solution with a mass ratio of 100:19:0.5; the two mixed solutions corresponding to the quartz series glass fiber cloth are a benzyl alcohol / anhydrous ethanol mixed solution with a mass ratio of 100:28, and a benzyl alcohol / anhydrous ethanol / surfactant mixed solution with a mass ratio of 100:28:0.5.
[0081] It can be seen from Table 3 that the addition of surfactants in the mixed solution can reduce the surface tension of the solution and facilitate the penetration of the glass fiber cloth, thereby reducing the sample immersion time and improving the detection efficiency by more than 30%.
Claims
1. A method for detecting hollow fibers in electronic grade glass fiber cloth, characterized in that: The following steps are involved: S1 sampling; S2 prepares a mixed solution of benzyl alcohol and anhydrous ethanol; S3: soaking the sample in step S1 in the mixed solution in step S2; S4 observes the number of bright lines in the sample under light, which is the number of hollow fibers in the electronic grade glass fiber cloth.
2. The method for detecting hollow fibers in electronic grade glass fiber cloth according to claim 1, characterized in that: In step S2, for the glass fiber cloth of the Low Dk series, the mass ratio of benzyl alcohol to anhydrous ethanol is 100:(19-23); for the glass fiber cloth of the quartz series, the mass ratio of benzyl alcohol to anhydrous ethanol is 100:(28-32).
3. The method for detecting hollow fibers in electronic grade glass fiber cloth according to claim 2, characterized in that: In step S2, the mixed solution further includes a surfactant. For glass fiber cloths of the Low Dk series and the quartz series, the mass ratio of benzyl alcohol to the surfactant is 100:(0.5-1.5).
4. The method for detecting hollow fibers in electronic grade glass fiber cloth according to claim 3, characterized in that: The surfactant is polyoxyethylene octylphenol ether.
5. The method for detecting hollow fibers in electronic grade glass fiber cloth according to claim 1, characterized in that: In step S3, the soaking time is 40-60 minutes.
6. The method for detecting hollow fibers in electronic grade glass fiber cloth according to claim 1, characterized in that: In step S1, when sampling, 5 samples with a size of 15 cm×25 cm in the warp direction×weft direction are taken from the entire cloth width.
Citation Information
Patent Citations
Electronic-grade glass cloth and method for testing holes of monofilaments of yarns
CN101864665A
Device and method for detecting hollow fibers of glass fiber electronic cloth
CN113445296A
Transparent composite substrate and display element substrate
US20140242865A1